THE EFFECT OF FINANCIAL PERFORMANCE AND ENVIRONMENTAL PERFORMANCE ON ISLAMIC SOCIAL REPORTING DISCLOSURES (Study of Mining Sector Companies Listed in List of Sharia Securities for the Period 2014-2018) - Alif Prakasa; Kurnia Rahman Abadi (University of Darussalam Gontor, 2019)
This research was conducted to examine the effect of independent variables namely financial performance usingindicators NetProfit Margin (NPM), Return On Assets (ROA), Return On Equity (ROE), Earning Per Share (EPS) and environmental performance using the indicator of the Company Performance Rating Program (PROPER) on disclosure of the dependent variable namely Islamic social reporting (ISR) mining companies registered in the sharia securities list for the period 2014-2018. The population in this study amounted to 25 mining companies listed on the Islamic(Maulana,2019) securities list in the 2014-2018 period. The sampling technique used purposive sampling method and obtained as many as 10 mining companies with a total sample of 50 research data. This study uses secondary data, namely annual reports, financial reports and reports from the Ministry of Environment (KLH) regarding the Corporate Performance Rating Program (PROPER) of mining companies registered in the Sharia securities list for the period 2014-2018. The analysis technique used is using multiple regression analysis with Statistical Product Service Solution (SPSS) 25 program. The results showed that the positive effect on the financial performance disclosure Islamic Social Reporting (ISR) are not supported due to a lack of enterprise performance management in legitimating religion and government policies, through the award approach. Environmental performance has a positive effect on unconfirmed disclosure of the Islamic Social Reporting (ISR) due to the lack of government approaching education and labor training on the mining environment.